Effectiveness of Cognitive Behavioral Therapy (CBT) in Managing Postpartum Depression: A Scoping Review of Comparative Interventions - Sugiyani, Sugiyani; Larasati, Disa; Aristawati, Tustika; Maulina, Rufidah; Septiana, Yesika Cahya; Meinawati, Khairunnisa; Kusumastuti, Wijayanti; Cantikasari, Sholikhawati Nur; Mustafa, Alifa Istu; Azka, Millati (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2025)
Background: Postpartum Depression (PPD) is a mood disorder experienced by mothers after childbirth that interferes with daily functioning. Cognitive Behavioral Therapy (CBT) has become the non-pharmacological intervention of choice in overcoming PPD. However, there is still a literature gap in systematic reviews regarding the effectiveness of CBT compared to other interventions in relieving PPD symptoms. Method: This study used a scoping review methodology following the PRISMA-ScR guidelines. A literature search was conducted across PubMed, ScienceDirect, and Cochrane databases, resulting in 91,664 articles using the keywords postpartum depression, PPD, Cognitive Behavioral Therapy, CBT, Edinburgh Postnatal Depression Scale (EPDS). Result: Four relevant articles were selected for analysis after the screening and critical appraisal process. The results of the analysis showed that various CBT methods, including digital applications, workshops, group therapy, and online courses, effectively reduced PPD symptoms with a success rate of 29-46%. Factors such as the duration of the intervention, the involvement of health workers, and therapist support contributed to the effectiveness of CBT and its impact on maternal well-being and mother-infant bonding. Conclusion: CBT has been shown to be an effective intervention in reducing PPD symptoms through both face-to-face and technology-assisted formats. Integrating CBT into routine maternal health services is recommended to enhance postpartum mental health outcomes and strengthen early parenting experiences.